THE EFFECT OF CLUSTERING TECHNIQUE ON WRITING EXPOSITORY ESSAYS OF EFL STUDENTS - Sabarun, Sabarun (Journal on English as a Foreign Language (JEFL), 2013)
The study is aimed at investigating the effectiveness of using clustering technique in writing expository essays. The aim of the study is to prove whether there is a significant difference between writing using clustering technique and writing without using it on the studentsâ writing achievement or not. The study belonged to experimental study by applying counterbalance procedure to collect the data. The study was conducted at the fourth semester English department students of Palangka Raya State Islamic College of 2012/ 2013 academic year. The number of the sample was 13 students. This study was restricted to two focuses: using clustering technique and without using clustering technique to write composition. Using clustering technique to write essay was one of the pre writing strategies in writing process. To answer the research problem, the t test for correlated samples was applied. The research findings showed that,it was found that the t value was 10.554.It was also found that the df (Degree of freedom) of the distribution observed was 13-1= 12.Â  Based on the Table of t value, if df was 12, the 5% of significant level of t value was at 1.782 and the 1% of significant level of t value was at 2.179. It meant that using clustering gave facilitative effect on the studentsâ essay writing performance.Keywords: reading comprehension, text, scaffolding